Shooting 007 and other celluloid adventures - Mills, Alec 1932-2024 (The History Press, 2014)
In this book, cameraman and director of photography Alec Mills, a veteran of seven James Bond movies, tells the inside story of his twenty years of filming cinema's most famous secret agent. Among many humorous and touching anecdotes, Mills reveals how he became an integral part of the Bond family as a young camera operator on 1969's On Her Majesty's Secret Service, how he bore the brunt of his old friend Roger Moore's legendary on-set bantering and how he rose to become the director of photography during Timothy Dalton's tenure as 007. Mills also looks back on a career that took in Return of the Jedi on film and The Saint on television with wit and affection, and the book contains many of his and Eon Productions' unpublished behind-the-scenes photographs compiled over a lifetime of filmmaking. Featuring many of the film industry's biggest names, this book is a must-have for both the James Bond and British film history aficionado
The early years -- War and Peace -- Carlton Hill Studios -- The Navy Lark -- Duty Calls -- Deliverance -- Back to work -- The sleeping tiger -- Harry Waxman BSC -- Father Brown -- Lost -- Contraband spain -- Moby Dick -- House of secrets -- Strange goings on -- Robbery under arms -- Third Man on the Mountain -- FLashback ... -- Swiss Family Robinson -- The Roman Spring of Mrs Stone -- Walt Disney -- Blow-up -- Moving on ... moving up -- On Her Majesty's Secret Service -- The hunting party -- The tragedy of Macbeth -- A Former Dweller -- A family thing -- Gold -- The hiding place -- Operation daybreak -- Shout at the devil -- Seven nights in Japan -- The Prince and the Pauper -- My 'mate' Ollie -- The spy who loved Me -- Coincidence ? -- Death on the Nile -- Moonraker -- A Cardiff paint job -- Avalanche Express .. the awakening -- Running scared -- Visit to a chief's son -- Sphinx -- Eye of the needle -- For your eyes only -- Return of the Jedi -- On the third day -- Negotiating salary -- Meet Jim ... or perhaps James ? -- Octopussy: my private Revolution -- Hot target -- Shaka Zulu -- Lionheart -- King Kong lives -- The living daylights -- Television flashbacks -- Licence to kill -- Bloodmoon -- Dead sleep -- A changing industry -- Christopher Columbus: the discovery -- Aces: iron eagle III -- Coincidence ... again ? -- The point Men -- Reflections -- Summing up -- The Phantom returns
Keywords: Mills, Alec / Anecdotes; Mills, Alec / Biography; James Bond films; Cinematographers; Motion picture authorship; Biografie